A TEACHING SEQUENCE BASED ON PROBLEM-BASED LEARNING AND FLIPPED CLASSROOM FOR TEACHING ELECTROCHEMISTRY IN HIGH SCHOOL - Santos, Hercília Araújo; Lima, Ezequiel da Cruz (Seven Editora, 2025)
The teaching of Electrochemistry in High School presents challenges related to the abstraction of concepts, the difficulty in articulating theory and practice, and student demotivation, especially when approached through traditional methodologies. Given this scenario, this work aimed to investigate the contributions of Problem-Based Learning and the flipped classroom to the teaching of Electrochemistry in High School. The methodology adopted was characterized as qualitative and bibliographic research, developed from the analysis of academic productions published between 2019 and 2025, located in the SciELO and Google Scholar databases, related to Chemistry teaching, active methodologies, and Electrochemistry. As a result, the literature analysis showed that the integration between Problem-Based Learning and the flipped classroom favors the contextualization of content, student protagonism, and the progressive organization of teaching, aspects relevant to the learning of electrochemical concepts. Based on these results, a theoretical teaching sequence was developed, structured in articulated stages aligned with the learning objectives of secondary education. It was concluded that the proposed approach contributes to lesson planning and reflection on substantial pedagogical practices in the teaching of Electrochemistry. DOI: https://doi.org/10.56238/sevened2025.036-141